The paradox of "remote working" in Covid-19 pandemic times: disability, inclusion, and accessibility in Brazil - Aydos, Val; Navarini, Daniela; Oliveira, Bernardo (Disability Studies Quarterly, 2021)
Due to the COVID-19 pandemic, many countries have adopted social isolation as a strategy to fight and limit the spread of the global crisis of Covid-19, which has impacted organization processes and employee's relationships with one another. Several issues such as the lack of accessibility and adaptations on work routines, that were already present in people with disabilities' life in the work environment are now highlighted, bringing to light theoretical debates and practical discussions about the experience of using technological accommodations as possible strategies for promoting accessibility and inclusion. Based on narratives of people with different corporalities in this contemporary shifting reality, in this article, we aim to reflect on how accessibility issues are being managed in labor practices in Brazil. More precisely, we seek to understand the role and effects of this new use of technology on social inclusion and exclusion of people with disabilities in the times and spaces where they work remotely due to the Covid-19 pandemic.